Impact of Activity Monitoring on Physical Activity, Sedentary Behavior, and Body Weight during the COVID-19 Pandemic - Jacob E. Barkley (International Journal of Environmental Research and Public Health, 2021)
Decreases in individuals’ physical activity and increases in sedentary behavior and bodyweight have been reported during the COVID-19 pandemic. The present study assessed the ability of physical activity monitoring, which may promote physical activity and discourage sedentary behavior, to mitigate these negative outcomes. An evaluation of university samples (N = 404, 40.5 ± 15.4 years) of self-reported physical activity, sedentary behavior, and bodyweight prior to the closure of campus due to the pandemic in March of 2020 and again at the time of the survey administration (May–June 2020) during pandemic-related restrictions was performed. Participants also reported whether they did (n = 172) or did not (n = 232) regularly use physical activity monitoring technology. While physical activity was unchanged during the pandemic (p ≥ 0.15), participants significantly increased sitting by 67.8 ± 156.6 min/day and gained 0.64 ± 3.5 kg from pre-campus to post-campus closure (p < 0.001). However, the use of activity monitoring did not moderate these changes. In conclusion, while physical activity was not affected, participants reported significant increases in sedentary behavior and bodyweight during the COVID-19 pandemic. These changes occurred regardless of whether participants regularly used physical activity monitoring or not.